The Effect of Acupressure Therapy at SP6 And LI4 Points on Lowering Blood Pressure in Elderly with Hypertension - Ni Nyoman Paramitha Dewintasari; I Wayan Mustika; I Ketut Sudiantara; Agus Sri Lestari; Komang Ayu Henny Achjar; I Ketut Gama; I Wayan Suardana; I Gusti Ketut Gede Ngurah; I Gusti Ayu Harini (Health Dynamics, 2025)
Background: Hypertension is a condition in which blood pressure is higher than normal values of ≥140/≥90 mmHg. Effective blood pressure control is the main goal to prevent and treat hypertension. In addition to pharmacological approaches, blood pressure can be controlled with non-pharmacological approaches such as acupressure therapy. This study aims to determine the effect of acupressure therapy at the SP6 and LI4 points on reducing blood pressure in elderly individuals with hypertension. Methods: This study was designed with a quasy-experiment with the type of research pre and post-test with control group with purposive sampling technique. Data were analyzed using the Wilcoxon test and the Mann-Whitney test. The population amounted to 81 elderly people with hypertension with the number of samples used in this study as many as 46 elderly samples with hypertension (23 in intervention group and 23 in control group). The majority of respondents were aged 65-69 years, female, worked as traders, and had elementary school education and did not go to school. Blood pressure was measured using a sphygmomanometer. Acupressure on SP6 and LI4 points was given to the intervention group for 3 weeks with a frequency of 2 times in 1 week, while the control group was given conventional treatment. Results: The results of the post-test difference in blood pressure between the intervention group and the control group with the Mann Whitney U-Test test showed a p-value = 0.000 (p <0.05), it can be concluded that there is a significant difference between the intervention group and the control group. Conclusions: The study concludes that there is an effect of acupressure therapy at point SP 6 and LI 4 on lowering blood pressure in the elderly with hypertension. It is hoped that the results of the study can be used as an alternative therapy in lowering blood pressure.